Heart and soul - Binchy, Maeve (New York : Alfred A. Knopf, 2009)
Dr. Clara Casey establishes a heart clinic that saves lives -- and heals her soul.
Keywords: Heart failure clinics -- Fiction; Dublin (Ireland) -- Fiction